Culture of Shame and Handling Violence Against Women - Abitha Arya Guna (POPULIKA, 2024)
Violence against women is an act that can occur in everyday life and can be experienced by anyone, especially women. One of the difficulties in handling violence against women is that victims of violence tend to have coping mechanisms, being reluctant to open up. Self-disclosure can be the key to dealing with violence. Victims and their families tend to cover up what they experienced because they feel ashamed and consider this violence to be a taboo subject to talk about. This research raises the issue of how a culture of shame influences the handling of violence against women. The research was conducted in Yogyakarta, which is still full of cultural values ​​and social norms. The research approach is a case study with interview and documentation data collection methods. From the research results, it was found that the politics of shame hinders the handling of violence against women. Keywords: Culture of Shame; Coping Mechanisms; Violence Against Women; Sexual Violence